Production and trade of opium in the Ottoman Empire, 1828-1838 - Matsui, Masako. (Thesis (M.A.) - Bogazici University. Institute of Social Sciences, 1995., 1995)
Opium was a product which dramatically changed Chinese history in the nineteenth century. Twice it caused war between Britain and the Qing Dynasty and forced the latter to sign the free trade treaty. The British exploitation of Indian opium is widely recognized yet the fact that the opium was also imported to China all the way from the Ottoman Empire is not well-known. Americans' attempts to enter the lucrative opium trade initiated Anatolian opium exports to China. The international opium trade network was established through the European expansion. The production of Turkish opium increased according to the demand in China and its trade proved to be profitable. This in turn caused the Ottoman Empire to impose a monopoly , Yed-i Vahid, on the trade of opium from 1828-1838 thus to increase its revenue which the empire was in desperate need to finance the incessant wars and reform movements at that time. The monopoly of trade, including opium, was abolished through the Free Trade Treaty signed between the Ottoman Empire and Britain in 1838, which promised the Ottoman Empire to acquire the British military support to fight against Muhammad Ali. As a result, however, the Free Trade Treaty began to deprive the empire of its revenue, such as the profit from the opium monopoly , causing difficulty in implementing the reform movement in the long run. The thesis tries to analyze this transformation of the opium trade and production in the Ottoman Empire both from international and internal perspectives.
Keywords: Opium trade -- Turkey.